2007
DOI: 10.1093/humrep/dem033
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of GnRH antagonist on Day 1 of stimulation as compared to the long agonist protocol in PCOS patients. A randomized controlled trial: effect on hormonal levels and follicular development

Abstract: BACKGROUND: The optimal time for GnRH antagonist initiation is still debatable. The purpose of the current randomized controlled trial is to provide endocrine and follicular data during ovarian stimulation for IVF in patients with polycystic ovarian syndrome (PCOS) treated either with a long GnRH agonist scheme or a fixed day-1 GnRH antagonist protocol. METHODS: Randomized patients in both groups (antagonist: n 5 26; long agonist: n 5 52) received oral contraceptive pill treatment for three weeks and a startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 23 publications
6
50
0
1
Order By: Relevance
“…Even though other studies reveal lack of association between IVF outcome and the LH level on the beginning [49,50] and during [51][52][53][54] COH, they did not concern PCOS patients. Study by Lainas et al [55] described significantly lower LH levels on days 3 and 5 and significantly higher LH levels on days 1, 7 and 8 of stimulation in the antagonist when compared with the agonist group among PCOS women. But these study did not consider the influence of LH on IVF outcome.…”
Section: Discussionmentioning
confidence: 95%
“…Even though other studies reveal lack of association between IVF outcome and the LH level on the beginning [49,50] and during [51][52][53][54] COH, they did not concern PCOS patients. Study by Lainas et al [55] described significantly lower LH levels on days 3 and 5 and significantly higher LH levels on days 1, 7 and 8 of stimulation in the antagonist when compared with the agonist group among PCOS women. But these study did not consider the influence of LH on IVF outcome.…”
Section: Discussionmentioning
confidence: 95%
“…The absence of pituitary suppression during the first few days of COS may have caused the follicular asynchrony, and starting the GnRH antagonist earlier during COS may theoretically improve asynchrony among follicles, thereby increasing the oocyte yield and eliminating the potential detrimental effects of early follicular exposure to LH and E 2 [8]. However, controversy emerged regarding whether earlier GnRH antagonist administration would increase the gonadotropin dose requirement, increase E 2 levels on the day of hCG, or have any effects on pregnancy outcomes and the incidence of OHSS [891121]. …”
Section: Discussionmentioning
confidence: 99%
“…Such a sample size (80 patients per group) is not easily achieved even in a multicenter study, when studying a small proportion of the population, such as PCOS patients who undergo IVF. The previous two studies on this topic reported 49 patients [10] and 78 patients [11] and we initiated this study because we thought we could provide useful clinical information, even with small number of subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral contraceptive [24,25,26] and luteal progesterone pretreatment [24] have also been studied in the same context. In addition, early initiation of the GnRH antagonist on cycle day 1 has been studied in normo- [27] or high-responding [28] patients. Recently, two studies evaluated the consequences on GnRH antagonist cycle dynamics of early follicular phase short-term antagonist administration [29,30].…”
Section: Discussionmentioning
confidence: 99%